2004
DOI: 10.2337/diacare.27.2.632
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Conversion From Bedtime NPH Insulin Injection to Once- or Twice-Daily Injections of Insulin Glargine in Type 1 Diabetic Patients Using Basal/Bolus Therapy

Abstract: Characteristics of patients with type 2 diabetes in Mexico: results from a large populationbased nationwide survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
61
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 3 publications
4
61
1
1
Order By: Relevance
“…2), with glucose tending to be lower before breakfast but rising to higher levels later in the day after oncedaily evening dosing. These observations are again consistent with those described by DeVries et al (11) with regard to studies of insulin glargine (15)(16)(17). As these glycemic profiles depict mean values, the implication is that some individuals will show a more extreme rise in glucose when treated with once-daily detemir, and it might be better for such individuals to be switched to twice-daily dosing.…”
Section: Nonrandomized 4-to 7-month Follow-upsupporting
confidence: 90%
See 1 more Smart Citation
“…2), with glucose tending to be lower before breakfast but rising to higher levels later in the day after oncedaily evening dosing. These observations are again consistent with those described by DeVries et al (11) with regard to studies of insulin glargine (15)(16)(17). As these glycemic profiles depict mean values, the implication is that some individuals will show a more extreme rise in glucose when treated with once-daily detemir, and it might be better for such individuals to be switched to twice-daily dosing.…”
Section: Nonrandomized 4-to 7-month Follow-upsupporting
confidence: 90%
“…As these glycemic profiles depict mean values, the implication is that some individuals will show a more extreme rise in glucose when treated with once-daily detemir, and it might be better for such individuals to be switched to twice-daily dosing. Again, this scenario has been described previously in studies involving insulin glargine (15,17,18).…”
Section: Nonrandomized 4-to 7-month Follow-upsupporting
confidence: 63%
“…Studies of glargine have reported that twice-daily administration of this basal insulin also tends to increase the dose. 22,23 The post hoc analysis in this trial suggested that similar proportions of patients in the 2 treatment groups met the protocol-defined criterion for a switch from a once-to twice-daily regimen (in the detemir group only). Thus, had this been mandated by the 18 protocol, the proportion of the glargine group completing the trial on a twice-daily regimen would have been similar to that in the detemir group (88.2% and 91.6%, respectively).…”
Section: Discussionmentioning
confidence: 80%
“…25 They found a significant reduction of 0.5% in HbA 1c values at one year. This study has several limitations as well.…”
Section: Discussionmentioning
confidence: 99%